Resistance pattern of some bacterial isolates from burns and wound infection: Pola resistensi beberapa isolat bakteri dari luka bakar dan infeksi luka - Reem Saad Ibrahim (Universitas Muhammadiyah Sidoarjo, 2024)
Wound and burn infections present ongoing challenges in healthcare due to multidrug-resistant bacteria. This study aimed to identify bacteria from these infections, assess antibiotic resistance, and evaluate treatment efficacy. Samples from 86 patients were cultured and tested for antibiotic susceptibility. Imipenem showed effectiveness against Gram-negative bacteria, while ciprofloxacin was more effective against Gram-positive bacteria. Rifampicin demonstrated reduced sensitivity. Staphylococcus aureus and Enterobacteriaceae were prevalent, indicating increasing multidrug resistance. These findings emphasize the need for tailored treatment strategies to combat antibiotic resistance effectively in wound and burn infections. Highlight: Resistance Challenge: Addressing antibiotic resistance in wound and burn infections. Tailored Treatment: Importance of customized approaches for effective antibiotic management. Predominant Pathogens: Identifying prevalent bacteria to guide targeted treatment strategies. Keywoard: Wound Infections, Burn Infections, Antibiotic Resistance, Bacterial Identification, Treatment Efficacy